2014
DOI: 10.1007/s11262-014-1062-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of an isolate of canine distemper virus from a Tibetan Mastiff in China

Abstract: Canine distemper (CD) is a highly contagious, often fatal, multisystemic, and incurable disease in dogs and other carnivores, which is caused by canine distemper virus (CDV). Although vaccines have been used as the principal means of controlling the disease, CD has been reported in vaccinated animals. The hemoagglutinin (H) protein is one of the most important antigens for inducing protective immunity against CD, and antigenic variation of recent CDV strains may explain vaccination failure. In this study, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
(12 reference statements)
2
21
0
1
Order By: Relevance
“…The present study clearly shows the distinct genetic relationships of Indian wild-type virus from vaccine strains and other known lineages of CDV around the world. H gene of a new CDV isolate TM-CC showed low identity (90.4 % nt and 88.9 % aa) with the H gene of the classical Onderstepoort vaccine strain and this could be one of the reason for host's inability to mount a protective immune response against CDV [14]. The observed diversity between the vaccine strains and the wild-type CDVs may be due to antigenic escape, genetic recombination between wild-type strains, adaptation to new host species that drive the evolution of the virus [8].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The present study clearly shows the distinct genetic relationships of Indian wild-type virus from vaccine strains and other known lineages of CDV around the world. H gene of a new CDV isolate TM-CC showed low identity (90.4 % nt and 88.9 % aa) with the H gene of the classical Onderstepoort vaccine strain and this could be one of the reason for host's inability to mount a protective immune response against CDV [14]. The observed diversity between the vaccine strains and the wild-type CDVs may be due to antigenic escape, genetic recombination between wild-type strains, adaptation to new host species that drive the evolution of the virus [8].…”
Section: Discussionmentioning
confidence: 94%
“…In F protein, maximum sequence variation was found in the signal peptide region (1-135 aa). Signal peptide region of F protein has the lowest amino acid homology and is reported to be geographically distinct [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that genomic differences occur between the wild-type CDV and the vaccine strains (Li et al, 2014). H gene is considered to be highly mutagenic (Martella et al, 2006).…”
Section: Introductionmentioning
confidence: 99%